NUCLEOTIDE MUTATIONS ANALYSIS OF MITOCHONDRIAL GENOME OF TWO INDONESIAN HUMAN INDIVIDUALS AND SEVERAL INDIVIDUALS FROM GENBANK - Ngili, Yohanis
Research related to the analysis of DNA and its application in various fields of science and technology is the leading branch of science because it helps answer the basic human problems of the present and future. Hipervariabel nature of mtDNA has been associated with the comparison of nucleotide sequences and mtDNA mutations among individuals, ethnic and age. However, hypervariable mutation occurred in mtG compared with rCRS (revised-Cambridge Reference Sequence) and hypervariable in various tissues of different origins such as layers entoderm, mesoderm, and ectoderm in certain individuals has not been reported previously. Also, it will compare nucleotide mutations in coding regions of genes, and seen new mutations or mutations that have not been reported in MITOMAP.